Macadamia (Macadamia integrifolia) Nut-Based Beverage: Physicochemical Stability and Nutritional and Antioxidant Properties - Juan Daniel Camacho-Teodocio; Tzayhri Gallardo-Velázquez; Guillermo Osorio-Revilla; Eduardo Castañeda-Pérez; Claudia Velázquez-Contreras; Maribel Cornejo-Mazón; Diana Maylet Hernández-Martínez (Beverages, 2024)
The present work presents an investigation of the effects of xanthan gum (XG) and soy lecithin (SL) on the physicochemical stability, fatty acid profile (FAP), and antioxidant capacity (AC) of macadamia nut-based beverages with thermal treatment (TT), as well as physicochemical changes during storage and sensorial acceptability. An extreme vertices mixture design was used, varying the macadamia nut, SL, and XG. The results show that adding XG and SL decreased the Sauter (D[3,2]) and Brouckere (D[4,3]) diameters of particles in macadamia beverages and increased the zeta potential (ZP), which represents greater stability. After applying TT in beverages, D[3,2], D[4,3], and ZP increased. After processing and TT, the FAP and fat nutritional indices changed due to reducing SFA and PUFA and increasing MUFA relative to macadamia nut. No significant difference (p ≥ 0.05) was observed in the FAP of beverages with and without TT. The AC determined by DPPH and ABTS decreased in most beverages upon TT application. During storage for two months, the beverage particle size increased, there was a decrease in brightness, and no significant difference (p ≥ 0.05) was observed in ZP. Sensory analysis showed that the most stable beverage was not the most acceptable due to its viscosity.